Europejska wielokulturowość i wielojęzyczność - Mejnartowicz, Agnieszka; Szmidt, Dorota T. (Investigationes Linguisticae, 2009)
The processes of economical, political and cultural integration to the European Union lead to the creation of a large area of interrelation among a large number of societies with different cultures and languages. This means that the traditional communication areas which have so far lived in some functional monolingualism will find themselves located in a unique interrelation process. One of the goals mentioned in the European Council documents is to promote the unity among the European societies and, at the same time, to preserve the current cultural and linguistical diversity. In the present paper we analyse the reasons for which it is necessary to protect the linguistical diversity and outlight the need to protect the European regional languages. We stream the importance of education in the “multiidentity” through the mutual knowledge of various languages and cultures which coexist in the European interrelation space.